The EPPO/OLAF compendium of national procedures: Greece - Hauck, Pierre; Schneider, Jan-Martin; Karakocaoğlu, Nur Sena; Laird, Alastair Alexander; Justus Liebig University Giessen (My University, 2026)
This Greek EPPO/OLAF volume provides a comprehensive collection of material including case law, legal sources and relevant institutions. It also contains a compendium of national legislation relating to EPPO investigations in Greece, highlighting the conduct of criminal investigations. The last part deals with OLAF’s investigations in Greece, focusing on the investigative missions. Dr Eftichis Fitrakis has acted as its national expert.
Keywords: ddc:340; ddc:320